Assessing the Impacts of Local Community Perceptions on Tourism Destinations in Uganda: A Case Study Lake Bunyonyi Kigezi Region (Uganda). - Turyatunga, Eric (2024)
Tourism development in Uganda, particularly in regions like Kigezi surrounding Lake Bunyonyi, has become increasingly important for economic growth. However, the success of tourism initiatives heavily relies on the perceptions and attitudes of local communities towards tourism activities. This study investigates the impact of local community perceptions on tourism destinations, with a focus on the Lake Bunyonyi surrounding community in the Kigezi Region. Utilizing qualitative research methods, including interviews and observations, data was gathered from community members, tourism stakeholders, and local authorities. The findings reveal a complex interplay of factors influencing community perceptions towards tourism, including socioeconomic benefits, environmental concerns, cultural preservation, and community empowerment. The study highlights the significance of community engagement and empowerment in fostering positive perceptions towards tourism. It underscores the importance of sustainable tourism practices that prioritize community involvement, cultural preservation, and environmental conservation. Moreover, the research identifies opportunities for collaboration between local communities, government agencies, and tourism stakeholders to enhance the socio-economic benefits of tourism while mitigating negative impacts. This research contributes to the understanding of community-tourism dynamics in Lake Bunyonyi and provides insights for policymakers, tourism practitioners, and community leaders to develop strategies that promote inclusive and sustainable tourism development in the Kigezi Region and beyond.